Physicochemical Characterization and Controlled Release Formulation on Intercalated 2-Methyl-4-chlorophenoxy Acetic Acid-Graphite Oxide (MCPA-GO) Nanocomposite - Norilyani Izzati Hasanuddin; Nur Nadia Dzulkifli; Siti Halimah Sarijo; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali (Indonesian Journal of Chemistry, 2020)
In this present work, herbicide named 2-methyl-4-chlorophenoxy acetic acid (MCPA) was intercalated into the graphite oxide through ion-exchange method to produce a MCPA-GO nanocomposite as an herbicide delivery system. The formation of MCPA-GO nanocomposite was confirmed by using PXRD, Fourier Transform Infrared Spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA), UV-Visible Spectroscopy and Accelerated Surface Area Surface (ASAP). As for PXRD pattern, there was increasing in the basal spacing of the nanocomposite from the graphite oxide which by 9.3 Å to 9.7 Å indicated that MCPA has succesfully inserted into the interlayers of the graphite oxide. Meanwhile, FTIR spectrum shown the appearance of a new peak in MCPA-GO nanocomposite at 1308 cm-1 represent the functional group of carboxylate (COO-).  This peak is very necessary for the confirmation of anionic form of MCPA inserted into the interlayers of graphite oxide. The controlled release property was also done for further investigation by using various aqueous medias to determine the percentage release of MCPA from the nanocomposite. The percentage of herbicide release in Na3PO3 solution was higher than in Na2CO3 and NaCl solution, proved that the release properties exhibits the potential application of graphite oxide as effective nanocarrier of herbicides. MCPA-GO nanocomposite suggested to be most promising herbicide since it can lower the toxicity of precursor MCPA, high biocompability, and more efficient in herbicide delivery system.